KUALITAS PRODUK, DESAIN PRODUK DAN KETEPATAN WAKTU TERHADAP KEPUASAN PELANGGAN BATIK PRINTING THOYIB SURAKARTA - Alviananda Permata Putri; Ida Aryati DPW; Supawi Pawenang (STIE Trisna Negara OKU Timur, 2022)
This study aims to determine whether there is a significant effect between the variables of product quality, product design and timeliness on ccustomer satisfaction on customer satisfaction of Batik printing Thoyib Surakarta. The methodsinsthis,research,uses quantitative,methods..Theppopulationiin this.study,wereccustomers of,batik printing thoyib surakarta, the sample used in the.study,was,100.respondents..The sampling technique used was,probability sampling with,a,random samplingpapproach. The author uses random sampling because it provides equal opportunities for each member of the population to be selected as a sample for this study.. The,dataatypesuuseddinnthislstudy. are.primary.and.secondaryddataaincluding observation, documentation, questionnaires, interviews and data collection technique usingliterature reviews. Theedataaanalysissmethods.innthissstudyyare.classical,hypothesis.testing,multiple,regression,analysis andltheecoefficienttoffdetermination.. The results oftthis,studylconcluded that the fluctuating producttqualitylhas a.positive and,significanttpositive impact on,customerssatisfacction a the results SPSS calculations are tcount > ttable (3,541 < 1,985) and;sig.of.0,001.is 'smaller,thann 0,005. Theeproductt.design variable,was declared to.have,a positivee and significant.effect,on,customer satisfaction because.the,result,of SPSSccalculationsoobtainedttcount > ttable (3,440 > 1,985) and sig of 0,001.is smaller than00,005. While thettimeliness variablehhas,appositive;andlsignificant effecton customer satisfaction because,the SPSSccalculation results’obtained,tcount > ttable (2,711 > 1,985)]and sig off00,008 is smaller thanp0,005. Keywords: Customer,Satisfaction, Product Quality, Product Design, Timeliness.